ERGATIVITY AND SUBJECT DELETION IN STYLISTIC-GRAMMATICAL CONSTRUCTIONS OF MINANGKABAUNESE - Jufizal (Jurnal Lazuardi, 2020)
In addition to grammatical-formal constructions, Minangkabaunese has another type of grammatical constructions in which the stylistic-cultural meanings are capsulated. Such stylistic-grammatical constructions bring about language politeness values, as well. This paper, which is derived from and developed based on a part of the result of a research conducted in 2017and in 2019, particularly discusses the phenomena of ergativity and subject deletion of the stylistic-grammatical constructions in Minangkabaunese in conveying language politeness value. Two questions are respectively answered in this paper: (i) what is the degree of ergativity of stylistic-grammatical constructions in Minangkabaunese?; and (ii) how do the ergativity and subject deletion convey the language politeness value and language education? The studies were descriptive-qualitative researches operationally conducted in the form of a field linguistic research. The data are in the form of syntactic constructions which are categorized into the stylistic-grammatical constructions. The result of data analysis reveals that: (i) the stylistic-grammatical constructions of Minangkabaunese have high degree of ergativity; and (ii) they bring about the languge politeness value by means of ergative construction, subject deletion, and using ready-made and fixed constructions. These are all useful for language education, especially in Minangkabaunese and in other languages with the same or similar culture.